1968
DOI: 10.1111/j.1744-7348.1968.tb04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bulb fly, Leptohylemyia coarctata Fall., and its effect on the growth and yield of wheat

Abstract: SUMMARYIn two experiments done in successive years to compare the growth and yield of Cappelle wheat either protected from or exposed to attacks by larvae of wheat bulb fly, the plots were previously fallowed, but egg laying was prevented on half of each plot by using Polythene soil covers. In the first season wheat was sown at the end of October, November and December and in the second season in late October and in early January, when there were two sowings, one with and one without a spring application of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…With the comparatively low degree of attack there would have been little competition between larvae for access to the plants and it seems likely that larval invasion was at random, with little preference for well tillered plants. Previous workers (Raw, 1954;Bardner, 1968) have shown that the number of shoots present at the time of larval invasion influences the survival of the larvae as they migrate from the egg to the host.…”
Section: Resultsmentioning
confidence: 99%
“…With the comparatively low degree of attack there would have been little competition between larvae for access to the plants and it seems likely that larval invasion was at random, with little preference for well tillered plants. Previous workers (Raw, 1954;Bardner, 1968) have shown that the number of shoots present at the time of larval invasion influences the survival of the larvae as they migrate from the egg to the host.…”
Section: Resultsmentioning
confidence: 99%
“…This will hinder the formation of the bud. But once the bud is formed, growth has started, and even if destroyed the bud may be replaced and further growth again takes place (Bardner 1968). Leaf injuries may be greater in a crop of about 2 weeks, or 5 days before bud initiation, because the leaves are more tender than in older plants.…”
Section: Resultsmentioning
confidence: 98%
“…However, when mites were introduced at later growth developmental stages (canolaÑthird true leaf stage; wheatÑGS14), plants were generally unaffected by mite feeding damage. This pattern highlights the susceptibility of early growth stages to herbivory with limited ability to compensate immediately after germination; however, as plant growth proceeds they become increasingly tolerant to attack (Bardner andFletcher 1974, Trumble et al 1993). Similar patterns have been shown previously on wheat.…”
Section: Discussionmentioning
confidence: 95%
“…Similar patterns have been shown previously on wheat. For instance, wheat seedlings with a single shoot are much more easily killed by the wheat bulb ßy (Leptohylemyia coarctata Fall) than older seedlings with two or more shoots (Bardner 1968).…”
Section: Discussionmentioning
confidence: 99%